Gender differentials among tobacco farmers and household welfare in Kuria East and West Sub-Counties, Kenya. - Marwa, Muniko Zephaniah; Mwangi, Samson Wokabi; Bor, Eric Kiprono (Advances in Social Sciences Research Journal, 2018)
The main focus of this study was to evaluate the effects of gender differentials between female and male headed households in tobacco production on socio-economic welfare of the household in Kuria East and West Sub-Counties. The social dilemma in this study was that household gender-labour relations were affected by tobacco production, which eventually affected other important household features such as socio-economic status and welfare necessities amongst tobacco farmers in Kuria Sub-Counties. Therefore, at the onset, this study investigated how tobacco production dynamics operated at the household level, mainly premised in gender-labour relations that were anchored in socio-cultural practices. This study was a sociological examination of a tobacco growing peasantry in Kuria Sub-Counties which concentrated on gender-labour relations between men and women for whom tobacco had become an important part of their existence as small-scale agricultural contract producers for the tobacco companies. All this was done at the behest of tobacco multinationals with capitalist hegemony that was supported by Government of Kenya at their beginnings. Specifically, the socio-economic aspects of the household were taken into consideration in the cash crop production, especially tobacco, which has raised interesting welfare issues that led to this study. Several factors were established and lead to the justification of this study. For instance, it was established that gender-labour relations in Kuria Sub-Counties were affected significantly by tobacco production whereby women were twice as likely as men to be involved in tobacco related farming activity in which their labour and welfare imperatives varied from household to household. On the other hand, this study also determined gender distribution of work in the household, that it particularly had bias on women and mainly disadvantaged them in Kuria Sub-Counties. This was premised in the fact that tobacco was a dominant cash crop in the society. It emerged that women needed to be empowered in Kuria Sub-Counties in order to participate fully in household decision making processes. In addition, this study established that female headed households had good welfare considerations in comparison with male headed households. Also, that male heads of households had institutionalized gender restrictions and constrained women regarding access household resources especially the benefits accrued from tobacco sales. This factor seemed to accrue long term significant implications for socio-economic welfare of the male headed households in Kuria Sub-Counties. Thus, the emphasis of this study was placed on gender-labour relations anchored on the socio-economic and cultural changes that have occurred and affected household welfare in Kuria Sub-Counties for several decades.